Electrochemical deposition technology regulating the morphology of hydroxyapatite deposited on silk fibroin film - WANG Tianyun; ZHANG Qing; ZHU Liangjun; YANG Mingying (浙江大学学报. 农业与生命科学版)
In order to investigate the morphology of hydroxyapatite (HAp) on the surface of silk fibroin (SF) film regulated by electrochemical deposition process, the effects of deposition time, ampere density and electrolyte pH on HAp morphology were discussed. Scanning electron microscope (SEM), electron diffraction spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR) and X-ray diffractions (XRD) were applied to characterize the morphology, Ca/P, chemical structure and crystalline phase of HAp. The results indicated that the thickness of HAp was increased by prolongation of deposition time, and the size of synthesized particles and pores was also increased with the rise of ampere density and electrolyte pH. A uniform, flat and porous surface of HAp was obtained with the ampere density of 2.5 mA/cm2, electrolyte pH of 5.3, deposition time of 30 min. This study expands the research and application of HAp/SF biomaterials in bone tissue engineering, and provides novel ideas for developing bone repairing materials based on silk fibroin.